Are the metrics that companies use effective for monitoring supply chain sustainability? A closer look at cocoa and rice - Jones, Sarah; Sanchez, Andrea; Wickramaratne, Chaturangi; Wakaabu, Dirisa; Ivanova, Yovita; Minh, Thai Thi; Mockshell, Jonathan; Sánchez Choy, José G.; Steinke, Jonathan (2024)
In a globalized world, consumers need to rely on information provided by agri-food companies to assess the impacts of the food they eat. And consumer interest in eating responsibly is growing, as stories of agriculture-driven deforestation, pollinator declines, and inhumane worker conditions hit the headlines. Major markets are responding too, by starting to require that agribusinesses demonstrate their products meet environmental and social standards (Kinderman, 2020), with the EU law banning products linked to deforestation as a recent example (http://data.europa.eu/eli/reg/2023/1115/oj). Companies know they need to meet these market requirements and consumer demands, to stay competitive. Indeed, despite an initial cost spike to set up effective monitoring systems, firms benefit financially in the long term from sustainability reporting (Friske et al., 2023), as this helps expand their consumer base. Companies have responded by seeking sustainability certification (e.g. Organic, Fairtrade, Rainforest Alliance) or setting themselves sustainability targets and reporting against these. Certification remains a market niche in part due to the high costs, and has its limitations since no single certification scheme addresses social, environmental and economic sustainability dimensions. For this reason, companies seek to demonstrate their sustainability commitments using company-determined targets and monitoring systems. Yet within this space, there is no clear guidance or consensus across agrifood businesses on which targets to set, which indicators to use to measure progress towards them, and how to collect reliable data on these indicators cost-effectively. This makes it difficult to compare companies and products. It increases the likelihood that some companies are using outdated, unreliable or costly methods to collect data because of a lack of tools and knowledge transfer across regions and commodities. It also creates a risk that certain locally important negative impacts (e.g. water depletion, soil degradation, forced labour, and farmer debt-levels) are under-reported, and that the indicators in use are poorly suited to the agroecological, multifunctional farms of the future (e.g. yield measured in tons/ha is a metric well-suited to monocultures and not to agroforestry systems, where whole system yields should be captured). Companies along cocoa and rice supply chains are no exception and the way they choose to monitor sustainability impacts has worldwide importance. An estimated 5.9 million tons of cocoa is produced each year (FAOSTAT, 2022) and used in a range of products, with chocolate the best known and loved by the consumer, while 776 million tons of rice is produced and is a major staple providing approximately 20% of the world’s calories (FAOSTAT, 2022).